A Implementation of Internal Quality Assurance Standard Operating Procedures as an Effort to Improve Academic Performance in the Faculty of Education Science - Widiyanah, Ima; Supriyanto; Hitta Alfie; Eka Cahya; Salsa zahra (Darul Ilmi Bina Insan Foundation, 2024)
Abstract: This research aims to analyze the SOP model for internal quality assurance at the UNESA Faculty of Education and to develop an SOP model for implementing internal quality assurance within the Faculty. Article 52 of Law 12 of 2012 concerning Quality Assurance of Higher Education states that Higher Education Quality Assurance is a systematic activity to improve the quality of higher education in a planned and sustainable manner (Ministry of Law and Human Rights 2012). Indonesia is still considered low in terms of quality and quality of education, therefore quality assurance at the education level is very important to be implemented. The research method used is qualitative by conducting interviews in the Quality Assurance Cluster of FIP UNESA which has implemented a similar program, in addition to observation, data reduction, data display is also carried out in this study, so as to obtain accurate data. The results showed that SPMI FIP UNESA was successful and received criteria in accordance with the applicable SOP standards with a value of 88.81%. SPMI at FIP UNESA did several things to develop the SOP, including (1) conducting discussions and validation among various parties, (2) Ploting aspects of SOP assessment and (3) Implementing achievement targets and planning annual achievement targets.